(untitled) (Research, Society and Development, 2021)
On February 3, 2020, the country declared a Public Health Emergency of National Importance, due to an outbreak of pneumonia, called SARs-CoV-2, data on cases have been collected and made available by the State Health Departments since then and deaths. This study aims to outline the mortality profile of patients diagnosed with COVID-19 hospitalized in an ICU in the southern region of the Western Amazon and the correlation of the evolution of deaths with the prone position during hospitalization. This is a descriptive and retrospective cross-sectional study, with a quantitative approach through the collection of secondary data from medical records of patients hospitalized with a diagnosis of COVID-19 in the Intensive Care Unit (ICU) of a public hospital in the first 6 months of care. (June 6 to November 6, 2020). Outlining the profile of patients will help to understand the profile of hospitalized patients and what are the main impacts on mortality from COVID-19. The predominant profile of hospitalization and mortality due to COVID-19, in the study hospital, are males aged 60 years, indigenous, black and brown, with previous diseases, the most prevalent being SAH, DM and obesity. Regarding the prone position (PP), there was no significant difference when compared to PP in the first 48 hours or after 48 hours of OTI, however patients who evolved to PP had a high mortality rate, in view of who are more serious patients than the others.